Effect of motor imagery training and electromyogram-triggered neuromuscular electrical stimulation on lower extremity function in stroke patients: a pilot trial - Cho, Young-Seok; Kim, Won-Jin; Kim, Ji-Hoon; Park, Ji-Su (Journal of Physical Therapy Science, 2017)
[Purpose] To investigate the effect of motor imagery training and electromyogram-triggered neuromuscular electrical stimulation (MIT-EMG NMES) on the lower extremity function of stroke patients. [Subjects and Methods] This study recruited eight patients with hemiplegia due to stroke. All patients received MIT-EMG NMES for 20 min daily, 5 days per week for 4 weeks. Lower extremity function were assessed using the timed up-and-go (TUG) and 10-meter walk (10MW) tests. [Results] The results of TUG test decreased significantly from 20.5 ± 4.5 to 14.0 ± 3.5 s, while those of 10 MW test showed a significant decrease from 21.3 ± 4.5 to 15.5 ± 3.2 m. [Conclusion] This study suggests that MIT-EMG NMES is a new rehabilitation therapy for lower extremity recovery in hemiplegic stroke patients.